Digital Encyclopedia of Applied Physics 2019
DOI: 10.1002/3527600434.eap818
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Spin and Transverse Momentum in Structured Optical Fields

Abstract: It has been recently recognized that in addition to the conventional longitudinal angular momentum, structured (inhomogeneous) optical fields exhibit helicity‐independent transverse spin angular momentum (SAM) and an unusual spin (circular polarization)‐dependent transverse momentum, the so‐called Belinfante's spin momentum. Such highly nontrivial structure of the momentum and the spin densities in the structured optical fields (e.g. evanescent fields) has led to a number of fundamentally interesting and intri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 113 publications
0
8
0
Order By: Relevance
“…It is tempting to call it "momentum spin, " as a reciprocal to the "spin momentum" of Equation (29), but this may be confusing, and therefore, the term "extraordinary spin" will be used. Existence of extraordinary spin and momentum with directions different from the wave propagation is a characteristic feature of structured light and is attracting much attention [74]; their specific examples and possible applications are discussed below in the Evanescent Waves: Extraordinary Spin and Momentum section, Surface Plasmon-Polaritons section and the Applications of Structured Light section. The latter Equation (39) discloses an interesting relation between the s E and the vorticity [9,20] (curl) of the OM.…”
Section: Dynamical Characteristics Of the Paraxial Fieldsmentioning
confidence: 99%
“…It is tempting to call it "momentum spin, " as a reciprocal to the "spin momentum" of Equation (29), but this may be confusing, and therefore, the term "extraordinary spin" will be used. Existence of extraordinary spin and momentum with directions different from the wave propagation is a characteristic feature of structured light and is attracting much attention [74]; their specific examples and possible applications are discussed below in the Evanescent Waves: Extraordinary Spin and Momentum section, Surface Plasmon-Polaritons section and the Applications of Structured Light section. The latter Equation (39) discloses an interesting relation between the s E and the vorticity [9,20] (curl) of the OM.…”
Section: Dynamical Characteristics Of the Paraxial Fieldsmentioning
confidence: 99%
“…, regardless of how is it divided between the polarization components). This spin appears due to the field vector rotation in the longitudinal plane and its analogues were recently discovered in a series of structured optical fields [6,[10][11][12][13][14][15][16] as well as in structured fields of other physical natures [17][18][19]. By comparison with Eqs.…”
Section: Paraxial Beamsmentioning
confidence: 96%
“…In particular, a complex structure of electromagnetic momentum has been revealed: it consists of the orbital (canonical) and spin (virtual) contributions, reflecting the roles of spatial (orbital) and polarization (spin) degrees of freedom [6,5,10]; likewise, the electromagnetic spin can also be decomposed into physically meaningful parts, differently related to the field polarization. It is found that the polarization-dependent "spin momentum" (SM) p S shows an "extraordinary" behavior: it can be directed orthogonally to the predominant direction of light propagation [11][12][13][14][15][16]. Quite similarly, the "transverse" orientation is typical for the helicityindependent "extraordinary spin" (ES) s E associated with the rotation of the field vectors in the longitudinal plane [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years there has been a great deal of interest in the angular momentum carried by light [1][2][3]. It is now well understood that in addition to usual longitudinal angular momentum structured light can possess an extraordinary transverse spin angular momentum (SAM) [4][5][6][7][8][9][10][11]. While the transverse SAM is helicity independent, the transverse momentum can be sensitive to the helicity, opening up new possibilities for spin optics [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The rotating tip of the field vector in time in the plane of incidence results on transverse spin. All these features have been discussed at great length in several recent reviews [3,11,22,23]. One of the major directions that emerge is how to enhance the tiny Belinfante momentum.…”
Section: Introductionmentioning
confidence: 99%